Teacheras Remuneration and Their Attitude to Work in Cross River State (Global Journal of Management and Business Research, 2014)
This study examined the possible influence of teacher#x2019;s remuneration and their attitude to work in Cross River State. Two main hypotheses were formulated for the study and the main instrument were the "Teachers Remuneration and Attitude Questionnaire" (TRAQ). It was given both full and content validity by experts in measurement and evaluation before administration. The TRAQ were administered on ISO teachers using he random sampling technique. The responses obtained from the questionnaire were coded and the Chi-square statistical analyses were used to test the hypotheses. The significance at 0.05 level were also determined. The result showed that regularity in the payment of teachers salaries influenced their attitude to work while payment of remunerations to teachers had an insignificant influence on teachers attitude to work. Based on these findings, recommendations were made for improvement (International Journal of Social Science and Public Policy 2002:5(1) pp 108-113).